Efectos del cambio climático en la economía, el comercio internacional y la estrategia empresarial - Duarte Cueva, Franklin (Pontificia Universidad Católica del Perú, 2015)
The impact of climate change produces variations in the production of goods and services, modifies consumption patterns ofbuyers, affects the strategies of private companies and influences the environmental policies of governments. In this context, the return expected by shareholders or partners cannot be achieved due to uncontrollable factors that often generate threats or opportunities for companies, according to which industry they operate. On the other hand, international trade is affected by climate change by increasing sanitary and phytosanitary requirements of governments, retail business associations and consumers. This situation leads to redefine business strategies and to the implementation of standards by international organisms,directly or indirectly related to climate change, seeking to adapt or mitigate its effects on life in the planet.